Learning Vocabulary through Paper and Online-Based Glossary - Sari, Ratih Novita (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This study examined the effect of teaching glossary and personality traits on vocabulary learning. Two groups of students who had different personality (extroverted and introverted) were exposed to two types of glosses: paper and online-based glossary. The two groups underwent two-month treatment. Prior to and after the treatment, each group was given pre and posttest. In calculating the data, two-way ANOVA was used. The results of the study showed that extroverted students learned vocabulary better through paper-based glossary, while introverted students learned vocabulary better through online-based. Further research needs to be conducted to determine whether age influences the use of teaching glossary or not.